2020
DOI: 10.1007/s00198-020-05310-6
|View full text |Cite
|
Sign up to set email alerts
|

Harmonization of commercial assays for PINP; the way forward

Abstract: Osteoporosis (OP) is a condition where there is low bone density and microarchitectural deterioration which can predispose to fragility fractures. There is a wealth of literature on OP from the developed countries, but less so from Asia. This review will explore the field of OP research in SouthEast Asia with regard to the epidemiology, the diagnosis of OP and the role of laboratory tests in the management of OP, with emphasis on 25-dihydroxyvitamin D and bone turnover markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…One of the major issues that impede the implementation of these bone turnover markers (BTMs) in clinical practice is the lack of standardization between the different methods available on the market. For PINP, we have recently shown that the two automated methods, IDS-iSYS (Boldon, UK), and Roche Elecsys® total P1NP assay run on cobas e family instruments (Mannheim, Germany) provided results that could be used interchangeably, allowing the application of similar reference ranges whatever the method, which is an important finding for the routine use of biomarkers outside the United States [ 4 , 5 ]. Indeed, in that country, the only approved method is the Orion UniQ manual radio-immunoassay (Espoo, Finland), which presents a significant proportional bias compared to the two automated methods.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major issues that impede the implementation of these bone turnover markers (BTMs) in clinical practice is the lack of standardization between the different methods available on the market. For PINP, we have recently shown that the two automated methods, IDS-iSYS (Boldon, UK), and Roche Elecsys® total P1NP assay run on cobas e family instruments (Mannheim, Germany) provided results that could be used interchangeably, allowing the application of similar reference ranges whatever the method, which is an important finding for the routine use of biomarkers outside the United States [ 4 , 5 ]. Indeed, in that country, the only approved method is the Orion UniQ manual radio-immunoassay (Espoo, Finland), which presents a significant proportional bias compared to the two automated methods.…”
Section: Introductionmentioning
confidence: 99%
“…Several measurement methods for the serum P1NP assay are available globally, including manual immunoassays manufactured by Orion Diagnostics (Finland) measuring intact P1NP; that of Uscn, Life Science (China) measuring total P1NP; and automated assays manufactured by Immunodiagnostics Systems (IDS, UK) measuring intact P1NP and by Roche (Germany) measuring total P1NP [ 21 , 22 , 23 ]. Considering that the analytical method for serum P1NP assays used in clinical laboratories in Korea is an automated electrochemiluminescence immunoassay manufactured by Roche, the validation of the analytical methods used in this study will contribute to the generalizability of this study and the standardization of data about biomarkers in osteoporosis treatment in the Korean population [ 2 , 8 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the research shows that the choice of OP treatment medicine should be based on bone metabolic markers [24] [40]. Low conversion medicine are mainly promoting bone metabolism, while high conversion medicine are mainly inhibiting bone resorption [40]. The results show that zoledronic acid combined with teriparatide is better than the single medicine group in improving bone metabolism markers PINP and β-CTX.…”
Section: Zoledronic Acid Combined With Teriparatide In the Prevention Of Recurrent Fracture After Pkpmentioning
confidence: 99%